An adolescent with hereditary spherocytosis who presented with splenic infarction. (2nd July 2015) - Jones, Lara; Refai, Zafer; Linney, Mike
Abstract : A 16-year-old male patient with known hereditary spherocytosis presented with a 4-day history of chest pain and lethargy. On admission, he had a low-grade fever and was grossly anaemic; examination revealed splenomegaly. An ultrasound scan confirmed splenomegaly with areas of splenic infarction. Subsequent tests suggested possible Epstein-Barr virus infection. The patient recovered well and had a functional spleen on discharge. This case report presents an unusual complication of isolated hereditary spherocytosis.